JNK/c-Jun-driven NLRP3 inflammasome activation in microglia contributed to retinal ganglion cells degeneration induced by indirect traumatic optic neuropathy. (January 2021) - Chu, Xiaoqi; Wang, Chun; Wu, Zheng; Fan, Liting; Tao, Chunmei; Lin, Jiaqi; Chen, Shuang; Lin, Yongzhong; Ge, Yusong
Abstract: Background: Indirect traumatic optic neuropathy (ITON) is a major cause of permanent loss of vision after blunt head trauma. Neuroinflammation plays a crucial role in neurodegenerative diseases. The present study concentrated on JNK/c-Jun-driven NLRP3 inflammasome activation in microglia during the degeneration of retinal ganglion cells (RGCs) in ITON. Methods: An impact acceleration (IA) model was employed to induce ITON, which could produce significant neurodegeneration in the visual system. Pharmacological approaches were employed to disrupt JNK and to explore whether JNK and the microglial response contribute to RGC death and axonal degeneration. Results: Our results indicated that the ITON model induced significant RGC death and axonal degeneration and activated JNK/c-Jun signaling, which could further induce the microglial response and NLRP3 inflammasome activation. Moreover, JNK disruption is sufficient to suppress NLRP3 inflammasome activation in microglia and to prevent RGC death and axonal degeneration. Conclusions: ITON could promote JNK/c-Jun signaling, which further activates the NLRP3 inflammasome in microglia and contributes to the degeneration of axons and death of RGCs. JNK inhibition is able to suppress the inflammatory reaction and improve RGC survival. Although further work is needed to determine whether pharmacological inhibition of the NLRP3 inflammasome can prevent ITON, our findings indicated that such intervention could be promising for translational work. Highlights: ITON activated NLRP3 inflammasome and microglial response via JNK/c-Jun activation. Activated microglial response and NLRP3 inflammasome contributed to RGCs degeneration. JNK/c-Jun inhibition suppressed the inflammatory reaction and improve RGC survival in ITON.